2010
DOI: 10.1007/s10531-010-9930-x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of indigenous butterfly community following control of invasive alien plants in a tropical island’s wet forests

Abstract: Invasive alien species pose one of the highest threats to biodiversity, especially in isolated oceanic islands where high rates of both endemism and extinction risk also usually prevail. Few studies have investigated the impact of invasive alien plants on butterflies in insular ecosystems, despite butterflies representing a key indicator group for terrestrial arthropod diversity. Using the Pollard Technique, we quantified butterfly species richness and abundance in eight wet lowland forest areas invaded by ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Nonetheless, classical biocontrol resulted in a reduction in the target plant and increases in diversity in invaded areas, which is likely to impact other trophic levels due to the provision of additional niches (Florens et al . ). These impacts occurred in the absence of additional control and restoration efforts, such as seeding.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, classical biocontrol resulted in a reduction in the target plant and increases in diversity in invaded areas, which is likely to impact other trophic levels due to the provision of additional niches (Florens et al . ). These impacts occurred in the absence of additional control and restoration efforts, such as seeding.…”
Section: Discussionmentioning
confidence: 97%
“…Local extinctions of desirable native species accompanied by dominance of exotic species with strong impacts on ecosystem processes commonly have slowed or stopped recovery in both terrestrial and aquatic restorations (Florens et al 2010, Hilt et al 2010, Tanentzap et al 2009). For instance, a 70-year restoration of a shallow lake via reduction of nutrient loading reestablished some aspects of community structure, but owing to the regional loss of rare species, diversity remained lower than in the reference period (Louette et al 2009).…”
Section: Trajectories That Deviate From Target Goalsmentioning
confidence: 99%
“…Removal of tamarisk trees (Tamarix ramosissima Deneb) from riparian areas along a river in Colorado improved butterfly habitat but not all species responded to removal (Nelson and Wydoski, 2008). Florens et al (2010) studied the effect of removing invasive plants from an island forest and found that forests with invasives removed had much greater butterfly abundance and richness than unweeded forests. Here we report the effects of removing privet on butterfly communities and compare them to untreated, heavily invaded control plots and to ''desired future condition'' plots that never had extensive privet cover.…”
Section: Introductionmentioning
confidence: 99%